Influence of growth stage on activities of polyhydroxyalkanoate (PHA) polymerase and PHA depolymerase in Pseudomonas putida U - Zinn Manfred; de Roo Guy; Witholt Bernard; Ren Qun; Thöny-Meyer Linda (BMC Microbiology, 2010)
Abstract Background Medium chain length (mcl-) polyhydroxyalkanoates (PHA) are synthesized by many bacteria in the cytoplasm as storage compounds for energy and carbon. The key enzymes for PHA metabolism are PHA polymerase (PhaC) and depolymerase (PhaZ). Little is known of how mcl-PHA accumulation and degradation are controlled. It has been suggested that overall PHA metabolism is regulated by the β-oxidation pathway of which the flux is governed by intracellular ratios of [NADH]/[NAD] and [acetyl-CoA]/[CoA]. Another level of control could relate to modulation of the activities of PhaC and PhaZ. In order to investigate the latter, assays for in vitro activity measurements of PhaC and PhaZ in crude cell extracts are necessary. Results Two in vitro assays were developed which allow the measurement of PhaC and PhaZ activities in crude cell extracts of Pseudomonas putida U. Using the assays, it was demonstrated that the activity of PhaC decreased 5-fold upon exponential growth on nitrogen limited medium and octanoate. In contrast, the activity of PhaZ increased only 1.5-fold during growth. One reason for the changes in the enzymatic activity of PhaC and PhaZ could relate to a change in interaction with the phasin surface proteins on the PHA granule. SDS-PAGE analysis of isolated PHA granules demonstrated that during growth, the ratio of [phasins]/[PHA] decreased. In addition, it was found that after eliminating phasins (PhaF and PhaI) from the granules PhaC activity decreased further. Conclusion Using the assays developed in this study, we followed the enzymatic activities of PhaC and PhaZ during growth and correlated them to the amount of phasins on the PHA granules. It was found that in P. putida PhaC and PhaZ are concomitantly active, resulting in parallel synthesis and degradation of PHA. Moreover PhaC activity was found to be decreased, whereas PhaZ activity increased during growth. Availability of phasins on PHA granules affected the activity of PhaC.